2013
DOI: 10.1017/s0376892913000234
|View full text |Cite
|
Sign up to set email alerts
|

Synergies and trade-offs between ecosystem services in Costa Rica

Abstract: Environmental Conservation 41 (1): 27-36 C Foundation for Environmental Conservation 2013. The online version of this article is published within an open access environment subject to the conditions of the Creative Commons Attribution-NonCommercial-ShareAlike licence . The written permission of Cambridge University Press must be obtained for commercial re-use. doi:10.1017/S0376892913000234 Synergies and trade-offs between ecosystem services in Costa Rica

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 64 publications
2
68
1
Order By: Relevance
“…Forest conservation and the maintenance of heterogeneous agricultural landscapes, with shade trees, windbreaks, live fences, weed strips, and protection of native plants that provide food resources and nesting sites and materials, are no-regret adaptation strategies. These strategies not only support future pollination service but also conserve biodiversity (23) and provide multiple ecosystem services today (24), such as water regulation and climate change mitigation (25,26). Managing a diverse, complex shade canopy could be a double-win that allows coffee to adjust to changes in climate while improving bee habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Forest conservation and the maintenance of heterogeneous agricultural landscapes, with shade trees, windbreaks, live fences, weed strips, and protection of native plants that provide food resources and nesting sites and materials, are no-regret adaptation strategies. These strategies not only support future pollination service but also conserve biodiversity (23) and provide multiple ecosystem services today (24), such as water regulation and climate change mitigation (25,26). Managing a diverse, complex shade canopy could be a double-win that allows coffee to adjust to changes in climate while improving bee habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Forest restoration scenarios in bottomland hardwood forests of the Mississippi River Basin showed clear spatial trade-offs between configurations targeting wildlife habitat and those targeted at improving water quality (Barnett et al 2016). A country-level study in Costa Rica showed that biodiversity hot spots have high co-benefits for carbon, water and scenic beauty, but areas with high carbon storage have lower co-benefits for water and scenic beauty (Locatelli et al 2014). Forest plantations for timber supply more provisioning services per unit area than natural forests, but offer fewer habitats for wildlife and lower levels of biodiversity ).…”
Section: Tools For Modeling Synergies and Trade-offs Between Ecosystementioning
confidence: 99%
“…Spatial targeting has been increasingly recognized as an important strategy for achieving additional gains for biodiversity (Busch and Grantham 2013;Locatelli et al 2013;Venter et al 2013). Studies in Tanzania (Lin et al 2014) and Brazil (De Barros et al 2014) show evidence of REDD+ initiatives spatially targeting high-biodiversity areas instead of purely carbon-rich areas.…”
Section: Biodiversity Do No Harm Additional Benefits Opportunity Realmentioning
confidence: 99%
“…There is also evidence that focusing REDD+ initiatives in highbiodiversity areas promotes more opportunities for bundling with other ecosystem services (e.g. biodiversity conservation, carbon storage, water regulation and scenic beauty) than when focusing on high-carbon areas alone (Locatelli et al 2013). …”
Section: Biodiversity Do No Harm Additional Benefits Opportunity Realmentioning
confidence: 99%